1994
DOI: 10.3109/00016349409006277
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal mesotheliomas in Danish women:

Abstract: An unexpectedly large number of peritoneal mesotheliomas among women was reported to the Danish Cancer Registry during the years 1960 through 1985. In a case-control study, we tested whether this was due to diagnostic misclassification or to direct exposure of the peritoneal membranes to talc during abdominal surgery. Tissue specimens were available from 96 reported peritoneal mesotheliomas; 35 cases (37%) were regarded as verified mesotheliomas, and 33 (34%) as possible mesotheliomas. Information on any intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In a Danish study about 30% of the peritoneal mesothelioma cases among women were found to be misclassified ovarian or gastrointestinal tumors (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Danish study about 30% of the peritoneal mesothelioma cases among women were found to be misclassified ovarian or gastrointestinal tumors (23).…”
Section: Discussionmentioning
confidence: 99%
“…However some misclassification of mesothelioma cases has occurred (23), and this misclassification complicates the interpretation of the results. …”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of peritoneal mesothelioma is difficult, both clinically and histopathologically, and incomplete biopsy material may lead to uncertainty. In a study of peritoneal mesotheliomas in Danish women, about 30% of the peritoneal mesothelioma cases were found to be misclassified ovarian or gastrointestinal tumors 29. Misclassification may probably also occur the other way around, although the extent of this has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Nielsen et al (1994), based on a large series of peritoneal mesotheliomas, estimated that 16% of cases were misdiagnosed as ovarian cancer cases. Assuming that a similar proportion of peritoneal mesotheliomas are misclassified as ovarian cancer cases, we evaluated the effect of misclassification on the overall pooled SMR estimate by removing 20% of ovarian cancer cases from every study and repeating the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%